2013
DOI: 10.1002/adfm.201301649
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Triphosphates as Promoters to Enhance Nanoceria Enzyme‐like Activity and for Single‐Nucleotide Polymorphism Typing

Abstract: Nucleoside triphosphates (NTPs) can improve the oxidase‐like activity of nanoceria and the enhancement is correlated with the type of NTP. This effect is demonstrated to be as a result of the coupling of the oxidative reaction with the NTP hydrolysis reactions, as the nanoceria has both oxidase‐like and phosphatase‐like activities. The differences reflect the different dephosphorylation catalytic activities of nanoceria to the NTP used. Furthermore, based on the NTP‐promoted oxidase‐like activity of nanoceria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 69 publications
0
90
0
5
Order By: Relevance
“…In the past decade, gold nanoparticles (AuNPs) [4][5][6][7], magnetic iron oxide NPs [8], and cerium oxide NPs (nanoceria) have been reported to mimic various enzymes [9][10][11][12][13][14][15][16]. Oxidation of glucose by AuNPs was first reported by Comotti et al in 2004 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, gold nanoparticles (AuNPs) [4][5][6][7], magnetic iron oxide NPs [8], and cerium oxide NPs (nanoceria) have been reported to mimic various enzymes [9][10][11][12][13][14][15][16]. Oxidation of glucose by AuNPs was first reported by Comotti et al in 2004 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Qu and colleagues 71 reported that nucleoside triphosphates (NTPs) can improve the oxidase-like activity of CeONP and that the enhancement is correlated with the type of NTPs ( Figure 5C). This effect was demonstrated to be a result of the coupling of the oxidative reaction with the NTPs' hydrolysis reactions, because CeONP has both oxidase-like and phosphatase-like activities.…”
Section: Biological Applications Bioanalysismentioning
confidence: 99%
“…9,[19][20][21][22][23] The best known examples are gold nanoparticles for glucose oxidation, 9 and CeO2 nanoparticles (nanoceria) that oxidize a diverse range of substrates. 20 Oxidase nanozymes are important since they do not require unstable H2O2 as a co-substrate.Nanoceria is a versatile nanozyme, displaying oxidase, 16,20 catalase, 24,25 superoxide dismutase, 26,27 and phosphatase 28 activities under different conditions. In 2009, Asati and co-workers first reported the oxidase-like activity of nanoceria.…”
mentioning
confidence: 99%
“…The catalytic activities of nanoceria were attributed to the mixed oxidation states of Ce 3+ and Ce 4+ , and related oxygen vacancies. 29,30 The role of redox states, 24 surface coating, 20 pH, 31 buffer composition, 32 and nucleotide triphosphate 16 were investigated. We hypothesize that surface chemistry plays a critical role in modulating substrate/product adsorption and electron transfer, thus influencing catalytic efficiency.…”
mentioning
confidence: 99%